Determinação das deformações residuais longitudinais decorrentes das tensões de crescimento em Eucalyptus spp. - Beltrame, Rafael (2010)
This study was developed with the objective to determinate the longitudinal deformations (DRL) resulting from growth stresses in standing and living trees in different clones of Eucalyptus spp. To do this, 12 clones of 9 years-old Eucalyptus spp., were selected, through annual increment means, which were planted at a spacing of 3.0 x 2.7 m. For measurements the variables of this research, 12 trees of each clone were selected, which the some variables were measured: basic density, bark thickness, diameter and total height. The measurements of longitudinal residual strain (DRL) were made in living trees with the extensometer (Growth Strain Gauge) using the CIRADForêt method. The readings were taken at four locations around the trunk of the tree following the guidance of planting (row, between rows). The measurements in the presence of winds were avoid, because with the movement of the tree, the support forces swing inside the trunk, changing the value recorded on the device. For levels of DRL, the results obtained in the study indicated that the clones had large variations between each other, and these had an average value considered high when compared with the literature. The clone 8 produced the lowest levels of deformation and it was considered an excellent genetic material. The clone 1 obtained the highest values of DRL. DRL variation occurred along the circumference of the tree trunk, and it was more pronounced on the east position. Analyzing the correlations among variables, it was found that the DRL was significantly correlated with the bark thickness, diameter and volume of standing tree. Basic density and height didn t have influence on the longitudinal residual strain. Some regression models were adjusted for DRL according to the bark thickness, diameter, height and volume to explain the behavior of this variable for each clone. Just for the basic density was not possible to set a significant model.